2022
DOI: 10.1038/s42003-022-03566-8
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine modification of the Aedes aegypti transcriptome and its alteration upon dengue virus infection in Aag2 cell line

Abstract: The N6-methyladenosine (m6A) modification of RNA has been reported to affect viral infections. Studies have confirmed the role of m6A in replication of several vector-borne flaviviruses, including dengue virus (DENV), in mammalian cells. Here, we explored the role of m6A in DENV replication in the mosquito Aedes aegypti Aag2 cell line. We first determined the presence of m6A on the RNAs from mosquito cells and using methylated RNA immunoprecipitation and sequencing (MeRIP-Seq) identified m6A modification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…It has been reported that the conserved region of METTL3 and METTL14 is the MT‐A70 domain, and the conserved region of YTHDC and YTHDF is the YTH domain (Du et al, 2016, p. 4; Zaccara et al, 2019). These two highly conserved domains are also present in the mosquito m 6 A‐related gene (Dai et al, 2022). Phylogenetic analysis also showed that the genes of the abovementioned four enzymes in mosquitoes have high similarity with the homologous genes in other species selected (Dai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the conserved region of METTL3 and METTL14 is the MT‐A70 domain, and the conserved region of YTHDC and YTHDF is the YTH domain (Du et al, 2016, p. 4; Zaccara et al, 2019). These two highly conserved domains are also present in the mosquito m 6 A‐related gene (Dai et al, 2022). Phylogenetic analysis also showed that the genes of the abovementioned four enzymes in mosquitoes have high similarity with the homologous genes in other species selected (Dai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These two highly conserved domains are also present in the mosquito m 6 A‐related gene (Dai et al, 2022). Phylogenetic analysis also showed that the genes of the abovementioned four enzymes in mosquitoes have high similarity with the homologous genes in other species selected (Dai et al, 2022). In particular, all of them have the same conserved domains, and the evolutionary relationship of genes corresponds with the evolutionary level of species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, m 6 A methylation positively regulates gene expression. For instance, the abundance of ubiquitin carrier protein 9 (Ubc9) mRNA and its stability were decreased by the inhibition of m 6 A modification in Aedes aegypti (Dai et al, 2022).…”
Section: Dopamine Regulated By M 6 a Modification Correlated With Lab...mentioning
confidence: 99%
“…The m6A modification has been identified as an important regulator in regulating expression of lncRNAs [ 18 , 19 ]. However, limited studies have investigated the m6A modification during dengue infection [ 20 , 21 ]. It is important to understand how the host immune system reacts to infection and how the virus evades immune response for developing effective antivirals [ 22 ].…”
Section: Introductionmentioning
confidence: 99%